Review of the Genetic Basis of Jaw Malformations - Ahmed, Mairaj K.; Ye, Xiaoqian; Taub, Peter J. (Journal of Pediatric Genetics, 2016)
Genetic etiologies for congenital anomalies of the facial skeleton, namely, the maxilla and mandible, are important to understand and recognize. Malocclusions occur when there exist any significant deviation from what is considered a normal relationship between the upper jaw (maxilla) and the lower jaw (mandible). They may be the result of anomalies of the teeth alone, the bones alone, or both. A number of genes play a role in the facial skeletal development and are regulated by a host of additional regulatory molecules. As such, numerous craniofacial syndromes specifically affect the development of the jaws. The following review discusses several genetic anomalies that specifically affect the bones of the craniofacial skeleton and lead to malocclusion.
Keywords: malocclusion; mandible; maxilla; congenital; Treacher Collins; mandibulofacial dysostosis; Nager; Miller